2005
DOI: 10.2134/jeq2004.0455
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Canola and Sunflower Diet Amendments on Cattle Feedlot Manure

Abstract: Cattle (Bos taurus) producers can replace a part of the traditional diet of barley (Hordeum vulgare L.) grain/silage with sunflower (Helianthus annus L.) seeds or canola meal (Brassica napus L.)/oil to enhance conjugated linoleic acids (CLA) content in milk and meat for its positive health benefits. The objective of this study is to investigate the effects of feeding sunflower or canola to finishing steers on cattle manure chemical properties and volatile fatty acid (VFA) content. The control diet contained 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Manure VFAs were dominated by acetic, propionic, and butyric acids, which together accounted for about 95% of TVFA. This was in agreement with previous findings (McGinn et al, 2002;Hao et al 2005Hao et al , 2009). Valeric acid concentrations were significantly lower for bedded than nonbedded pens in June and July (p < 0.05).…”
Section: Background Weather Informationsupporting
confidence: 94%
“…Manure VFAs were dominated by acetic, propionic, and butyric acids, which together accounted for about 95% of TVFA. This was in agreement with previous findings (McGinn et al, 2002;Hao et al 2005Hao et al , 2009). Valeric acid concentrations were significantly lower for bedded than nonbedded pens in June and July (p < 0.05).…”
Section: Background Weather Informationsupporting
confidence: 94%
“…This has led to increased availability and use of dried distillers' grains with solubles (DDGS) as a livestock feed (Berger and Good 2007;Klopfenstein et al 2007). With the nitrogen content in DDGS approximately two to three times that of unprocessed grain (Spiehs et al 2002;Widyaratne and Zijlstra 2007), adding DDGS to livestock diets could potentially change the manure pH, N form and content, and C/N ratio, given that these properties are influenced by diet (Hao et al 2005b;Velthof et al 2005;Yan et al 2006;Maguire et al 2007;Hao et al 2009). Hao et al (2009) reported increases in manure pH, NH 4 ?…”
Section: Introductionmentioning
confidence: 99%
“…The plant nutrient content in livestock manure is influenced by the composition of livestock diets (Hao et al, 2005, 2009). Changing cattle feedlot diets by increasing the use of dried distillers’ grain with solubles (DDGS), a co‐product from the ethanol fuel industry, can increase N and P levels in manure and compost (Hao et al, 2009, 2011) and the potential for leaching losses following land application.…”
mentioning
confidence: 99%